Inhibition of arachidonic acid release from cells as the biochemical action of anti-inflammatory corticosteroids. - Hong, S L (1976)
Serum stimulates the production of prostaglandins by transformed mouse fibroblasts. Hydrocortisone (cortisol) inhibits this stimulation. The half-maximal inhibition occurs at 6x10-9 M. Studies with cells labeled with [3H]arachidonic acid in their lipids show that the stimulation by serum results in the release of arachidonic acid from the cellular lipids, mostly phospholipids. Hydrocrotisone inhibits this release but does not inhibit the production of prostaglandins from exogenously supplied arachidonic acid. This inhibition of arachidonic acid release from phospholipids may be the mechanism for the anti-inflammatory action of corticosteroids.